2009
DOI: 10.3201/eid1503.081131
|View full text |Cite
|
Sign up to set email alerts
|

Integron-mediated Multidrug Resistance in a Global Collection of NontyphoidalSalmonellaentericaIsolates

Abstract: Horizontal gene transfer and clonal expansion contribute substantially to the dissemination of resistant strains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 26 publications
7
67
0
4
Order By: Relevance
“…By querying the MLST database (http: //mlst.warwick.ac.uk/mlst/dbs/Senterica), we identified another 10 records of ST328 isolates, all of which were isolated from humans in Asia (Taiwan and the Philippines) and Europe (United Kingdom) in 2001 to 2007. As part of the study of integron-mediated resistance in a global collection of S. enterica isolates, Krauland et al have reported on clonal dissemination of ST328 S. Typhimurium isolates with the ACSSuT phenotype (resistance to ampicillin, chloramphenicol, streptomycin, sulfamethoxazole, and tetracycline) in Taiwan and the Philippines (55). However, it is not known whether any of the ST328 isolates from Asia or the United Kingdom exhibited resistance to oxyimino-cephalosporins or quinolones.…”
Section: Discussionmentioning
confidence: 99%
“…By querying the MLST database (http: //mlst.warwick.ac.uk/mlst/dbs/Senterica), we identified another 10 records of ST328 isolates, all of which were isolated from humans in Asia (Taiwan and the Philippines) and Europe (United Kingdom) in 2001 to 2007. As part of the study of integron-mediated resistance in a global collection of S. enterica isolates, Krauland et al have reported on clonal dissemination of ST328 S. Typhimurium isolates with the ACSSuT phenotype (resistance to ampicillin, chloramphenicol, streptomycin, sulfamethoxazole, and tetracycline) in Taiwan and the Philippines (55). However, it is not known whether any of the ST328 isolates from Asia or the United Kingdom exhibited resistance to oxyimino-cephalosporins or quinolones.…”
Section: Discussionmentioning
confidence: 99%
“…The esterase gene is part of the complex class 1 integron containing the Asian rifampin resistance gene, arr-2, which is also contained as a gene cassette (17). If this structure is stable, together with bla NDM-1 , it will act as a unique genetic marker for the prevalence and stability of plasmid pNDM-1 throughout Indian …”
Section: Discussionmentioning
confidence: 99%
“…Integrons are gene capture systems, most famous for their rapid acquisition and spread of antibiotic resistance genes. [70][71][72] Their common association with plasmids means they can be particularly promiscuous. [73][74][75][76][77][78][79] Integrons are essentially composed of: (1) a core stable platform of a site-specific tyrosine recombinase (integrase) gene (intI) with its own promoter (P int ) and an outward facing promoter (P C ) within the intI coding sequence that can express captured cassettes of gene(s), 80,81 and (2) an adjacent attI recombination site (Fig.…”
mentioning
confidence: 99%